Respuesta :
Answer:
[tex]x=-2[/tex]
Step-by-step explanation:
[tex]-5x+(-2)=-2x+4[/tex]
[tex]-5x+(-2)+5x=-2x+4+5x[/tex] (according to first step)
[tex]-2= 3x+4[/tex]
[tex]-2+(-4)=3x+4+(-4)[/tex] (according to second step)
[tex]-6=3x[/tex]
[tex]\frac{-6}{3}[/tex]=[tex]\frac{3x}{3}[/tex] (according to third step)
[tex]-2=x[/tex]
[tex]x=-2[/tex]
hence the solution of the given equation is [tex]x=-2[/tex]
Answer:
The answer is negative two.
Step-by-step explanation:
sorry i'm very late but this answer might help other people.
hope you have a good day.
:)